Behavior Analysis of Students in Utilizing Faculty of Agriculture Library, Gadjah Mada University - Hidayah, Laili; Junandi, Sri; Wahyuningsih, Yuli Hesti (Department Library of Governance Institut of Home Affairs, 2020)
Problem Statement: The behavior of students in utilizing the library is very diverse, so it needs to be examined further. Purpose: This study examines the extent of student behavior in using the library and what factors influence student behavior in utilizing the Library of the Faculty of Agriculture Universitas Gadjah Mada. Method: This research is descriptive qualitative and data collection uses observation, in-depth interviews and documentation. Result: The results of the study indicate that the behavior of students to the library is diverse in terms of attitudes, encouragement and expectations in using the library. The diversity of behavior is still in the library's goal as a source of learning, entertainment and research. Conclusion: The factors that influence the attitude of behavior using the Library are the environment, facilities, type of service, room, wifi access and staff. Students are of the opinion that these factors that influence it utilize the Library of the Faculty of Agriculture Universitas Gadjah Mada. Keywords: behavior, utilization, library, Faculty of Agriculture UGM